Implementasi Metode YOLOv5 pada Sistem Pendeteksi Jentik Nyamuk Berbasis IoT - Karimah, Savira; Tri Pangestu, Rafif; Febriansyah, Aan; Irwan, Irwan (Jurnal Inovasi Teknologi Terapan, 2024)
Indonesia is a tropical country that generally faces the risk of widespread mosquito distribution in each of its regions. With the abudance of mosquito distribution, the spread of mosquito larvae will also increase. As a result, mosquito larvae fins suitable places to breed in hard-to-reach areas. Therefore, a tool is needed to monitor these mosquito larvae when they are in water reservoir or containers that are difficult to access. The method used in this final project is You Only Look Once (YOLO). Based on the system can perform detection but is not yet working optimally. The system can detect well in places with bright light intensity or not too dark. The test result of this system show that it can detect many mosquito larvae at once. The accuracy results obtained from testing range from 51% - 89%.